Media Socialization Of Surakarta City Government Programs Through Shadow Puppet Shows In 2022 - Pradopo, Amar (Empowerment Society, 2024)
This research aims to determine the communication process of the socialization of the Surakarta City Government program using shadow puppet media in 2022. The research method uses a descriptive analysis approach with data collection methods through observation methods, interview methods, and literature study methods. The data obtained was analyzed descriptively and qualitatively consisting of data reduction, data presentation, and drawing conclusions. The research results show that communication is an important element in implementing wayang performance activities as a medium for socializing government policy programs. The communication process through puppets can run more easily, more comfortably, and on target. So that the socialization material order can be understood by the public. Puppets can be a means of communication between the government and the community (wayang audiences) in delivering programs, in this research the Law on Illegal Cigarettes program with the theme Gempur Illegal Cigarettes.